The Effect of Explicit versus Implicit Instructional Approaches during a Technology-Based Curriculum on College Students’ Understanding of the Nature of Science (NOS) - Alsaidi, Ahmed Alsaidi (Jordan Journal of Educational Sciences, 2008)
The purpose of this study was to examine the effect of explicit versus implicit instructional approaches on students’ understanding of the nature of science (NOS). The study emphasized the inferential and tentative NOS. The control group consisted of 97 students, 64 female and 33 male, and the experimental group consisted of 143 students, 92 female and 51 male. A quantitative analysis of students’ preintervention NOS views revealed that there was no statistically significant difference between implicit and explicit groups in both targeted NOS aspects, However, the same analysis indicated a statistically significant difference for postintervention between implicit and explicit groups, A qualitative analysis of students’ pre-intervention views of the target NOS revealed that the number of informed NOS responses was not considerably different. However, analysis of post-intervention NOS views indicated that more students in the explicit group demonstrated informed views of the target NOS than in the implicit group. The findings of the study demonstrated firstly, the effectiveness of the explicit approach when teaching aspects of the NOS and secondly, that this teaching could be accomplished through short intensive discussion.